The vortex of multiculturalism in South Korea: a critical discourse analysis of the characterization of "multicultural children" in three newspapers. Issue 1 (2nd January 2019) - Shin, Jaran
ABSTRACT: This study investigates how multicultural children have been portrayed by the Korean media, where the term is typically used to mean a child of an underprivileged Korean man and a female marriage migrant from a less industrialized neighboring country. Adopting the theoretical lens of critical discourse analysis, I examine news articles published from 2009 to 2013 in the Hankyoreh, the Hankook Ilbo, and the Chosun Ilbo : three daily newspapers representing a full range of progressive, moderate, and conservative political perspectives within society. Analysis reveals that multicultural children have been characterized as a marginalized group, as a threat to the future Korean society, or as global human resources. Given that these discourses are manifestations of underlying ideology, I also explore how these three discourses are conjoined with three competing ideologies in Korea; namely, democracy, nationalism, and neoliberalism. This study concludes by discussing how multiculturalism serves as a discursive framework through which democratic, nationalist, and neoliberal ideas gain their effectiveness.